2018
DOI: 10.1080/14712598.2018.1506761
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from lung and liver in-vivo gene therapy: implications for the future

Abstract: Introduction: Ex-vivo gene therapy has had significant clinical impact over the last couple of years and in-vivo gene therapy products are being approved for clinical use. Gene therapy and gene editing approaches have huge potential to treat genetic disease and chronic illness. Areas covered: This article provides a review of in-vivo approaches for gene therapy in the lung and liver, exploiting non-viral and viral vectors with varying serotypes and pseudotypes to target-specific cells. Antibody responses inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 104 publications
(123 reference statements)
1
41
0
Order By: Relevance
“…For intravenously injected GAd, lung is the first-pass organ, and our data are consistent with the notion that the pulmonary vascular ECs with high vector receptor abundance can sequester the viral particles in a saturable fashion before an excess dose bypassing the lung EC capacity can reach other organs (6,9). Gene therapy has long been a sought-after strategy for a range of acquired and inherited diseases of the lung, and yet it remains a major challenge for this approach to deliver a sufficient therapeutic payload to the organ to result in reversal or amelioration of disease symptoms (12,13). Interestingly, recent mouse vaccine study has shown that a GAd-based immunization vector induced potent and durable immune protection against respiratory infectious disease caused by respiratory syncytial virus (RSV) infection (5).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…For intravenously injected GAd, lung is the first-pass organ, and our data are consistent with the notion that the pulmonary vascular ECs with high vector receptor abundance can sequester the viral particles in a saturable fashion before an excess dose bypassing the lung EC capacity can reach other organs (6,9). Gene therapy has long been a sought-after strategy for a range of acquired and inherited diseases of the lung, and yet it remains a major challenge for this approach to deliver a sufficient therapeutic payload to the organ to result in reversal or amelioration of disease symptoms (12,13). Interestingly, recent mouse vaccine study has shown that a GAd-based immunization vector induced potent and durable immune protection against respiratory infectious disease caused by respiratory syncytial virus (RSV) infection (5).…”
Section: Discussionsupporting
confidence: 62%
“…In terms of specificity and efficiency of pulmonary gene delivery, the GAd vector is superior to the lungpreferred HAd5.MBP vector previously developed by our group (9-11) (also in Supplemental figure 3). In fact, the GAd vector may have been the best performing pulmonary gene delivery platform among various viral and none-viral systems described in the existing literature that the authors are aware of (12,13). While the precise molecular determinant of the virus tropism specificity remains to be elucidated, our viral capsid modification data suggested an involvement of fiber knob in modulating vector lung targeting efficiency.…”
Section: Discussionmentioning
confidence: 82%
“…In the ex vivo approach, patient-derived tumor cells are collected, propagated usually as 2D monolayers, manipulated genetically and then introduced back into the host [20]. In the in vivo approach, TNAs may be introduced in loco into the tumor cells, systemically via intravenous administration, or in a pre-systemic manner through oral, ocular, transdermal or nasal delivery routes, depending of the specific localization of tumors and disease progression [20][21][22]. In the case of systemic and pre-systemic deliveries, the administration of naked TNAs is hindered by biological barriers, nuclease susceptibility, phagocyte uptake, renal clearance and/or immune response stimulation [23].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of systemic and pre-systemic deliveries, the administration of naked TNAs is hindered by biological barriers, nuclease susceptibility, phagocyte uptake, renal clearance and/or immune response stimulation [23]. Hence, the use of stable carriers/vectors that protect the nucleic acid cargo from circulatory nucleases, avoid the immune system, and ensure the efficient targeting of the therapeutic vector into the tumor cells, without dissipation in the body through lymphatic and blood systems and avoiding non-target cells is required [21]. Despite the apparent limitations of the in vivo approach, it is less invasive and more suitable for cancer treatment than ex vivo approaches, since the latter require a proliferative advantage of transfected cells, which is antagonist to the major objectives of cancer gene therapeutics that mainly aims to inhibit the tumor progression by tackling the tumor cell division ability [21,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation